Struktur Komunitas Zooplankton di Ekosistem Lamun Alami dan Berbagai Lamun Buatan Perairan Teluk Awur, Jepara - Hibatul, Tasa; Riniatsih, Ita; Azizah, Ria (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Zooplankton are one component in the food chain as measured in relation to the productivity value of an ecosystem. This is because the zooplankton is a major connecting link between plankton and nekton. Teluk Awur Waters are shallow waters with depths less than 10 meters. These waters are also under pressure from various human activities. The aim of this research were to find out the community structure of Zooplankton on native and artificial seagrass ecosystems in Teluk Awur waters, Jepara. The method of this research was a case study method with the exploratory nature of data collection used Sample Survey Method. The location was set as a research Station was the Station 1, as the native seagrass, and Station 2, 3, and 4 as the artificial seagrass. Sampling was conducted every 2 weeks for 4 times of sampling of each 3 times making use planktonnet with mesh size 45 Î¼m. Sampling was carried out horizontally in the morning on July 2012 to September 2012. The results obtained 37 genera on native seagrass, while on the third of artificial seagrass was obtained 51 genera. Abundance obtained on the native seagrass was an average of 3845,482 specs/L and on the artificial seagrass was an average of 3146,303 specs/L. Diversity of zooplankton showed the medium diversity, an average of 2,08 obtained on the native seagrass and an average of 2,15 obtained on the artificial seagrass. Homogenity obtained average of 0,48 on the native seagrass and 0,50 on the artificial seagrass which is showed that the level of homogeneity is in medium range. The index of domination on the native seagrass was obtained an average 0,51 which is showed that the level of dominance is in medium range and on the artificial was obtained an average 0,49 which is showed that the level of dominance is in low range.